The political economy of economic growth in Africa, 1960-2000 - Ndulu, Benno J.; O'Connell, Stephen A.; Bates, Robert H. (Cambridge : Cambridge University Press, 2008)
The Political Economy of Economic Growth in Africa, 1960 - 2000 is the most ambitious and comprehensive assessment of Africa's post-independence economic performance to date. Volume 2 supports and extends the analysis of African economic growth presented in the first volume by providing twenty-six case studies of individual African economies.
Vol. 2 includes CD-ROM which includes 8 more chapters.
Includes bibliographical references and indexes.
rua 21/02/17
Loans
Keywords: Economic growth; Politics and government; Economic history; Economic policy; Africa